EFEKTIVITAS METODE KELOMPOK TERHADAP PERUBAHAN PENGETAHUAN WANITA TANI TENTANG TANAMAN OBAT KELUARGA DI KELURAHAN NAMBO KECAMATAN NAMBO KOTA KENDARI - Sukmawati Abdullah (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This study aims to determine the effectiveness of the use of group methods with a group approach to changing the knowledge of women farmers about family medicinal plants. This research was conducted in the Nambo Village, Nambo District, Kendari City which was determined purposively. The population of this research is women farmers who cultivate medicinal plants in the family, amounting to 20 people. The type of data is primary data obtained using a list of questions (questionnaire) and secondary data obtained from related agencies. The data processing method uses the effectiveness formula. The variables observed were (1) Respondent's identity including age, education level, number of family dependents, farming experience, land area, frequency of attending counseling, and cosmopolitan relations; (2) The effectiveness of the group method through the group discussion approach in agricultural extension activities with material on family medicinal plants; (3) Changes in the knowledge of women farmers about cultivation techniques, uses and benefits of family medicinal plants. The results of this study revealed that the effectiveness of using the group method on changes in the knowledge of women farmers about family medicinal plants, namely for turmeric plants (70.63%), ginger plants (72.41%), lemongrass plants (69.47%). The knowledge of women farmers about family medicinal plants has changed in terms of pre-test and post-test values, namely the total pre-test score is 441 and the total post-test score is 738.